Penyuluhan Pengenalan Mikroplastik dan Cara Mengurangi Paparannya Pada Air Minum dan Makanan Kemasan di Desa Perante - Udrika Lailatul Qodri (Lembaga Pengembangan Kinerja Dosen, 2025)
Microplastics pose a significant threat to aquatic ecosystems and human well-being. This study attempts to conduct a community engagement initiative that focuses on the dangers of microplastics, with the aim of raising public awareness and fostering sustainable behavior change in plastic waste management. Microplastic pollution has become a worrying problem because it has the potential to pose risks to food safety and public health. This study aims to conduct a socialization program on the dangers of microplastic exposure to food safety in the Kertosari Village community. Using a participatory approach, this socialization program involves local communities and students. Socialization activities include informative presentations and interactive discussions to raise awareness of the adverse effects of microplastics on food safety. The results of this community engagement are expected to be a valuable guide for authorities and local communities to raise awareness of the dangers of microplastics and encourage sustainable behavior change towards plastic waste management.